The glassy sweepers' way: seeking a versatile wrasse to be cleaned - Sazima, Cristina [UNESP]; Krajewski, João Paulo; Bonaldo, Roberta Martini; Sazima, Ivan (Sociedade Brasileira de Ictiologia, 2005)
Diurnal reef fishes compose the bulk of clients that seek cleaner fishes' services, but some nocturnal species that shelter at daytime also seek the cleaners. While doing so the nocturnal clients must leave their hiding places and thus they get exposed to potential diurnal predators. We report here on the cleaning interactions between a daytime cleaner wrasse (Thalassoma noronhanum) and a night time active client (Pempheris schomburgki) that usually remains sheltered at daytime. We recorded P. schomburgki leaving their shelter at daytime and heading towards T. noronhanum, whenever the cleaner swam by the shelter. Since T. noronhanum is able to tend temporary cleaning station near the safety of the shelters of its clients, P. schomburgki lessens a possible risk of predation by seeking this versatile cleaner.

Peixes recifais diurnos compõem a maioria dos clientes nas estações de peixes limpadores. Entretanto, algumas espécies com hábitos noturnos também procuram os peixes limpadores, ficando expostas a potenciais predadores diurnos quando precisam deixar seus abrigos. Registramos aqui as interações de limpeza entre um labrídeo diurno (Thalassoma noronhanum) e um cliente com hábitos noturnos (Pempheris schomburgki), que permanece abrigado durante o dia. Esta espécie de cliente deixa seu abrigo durante o dia e nada em direção a T. noronhanum quando este limpador desloca-se próximo aos esconderijos. Uma vez que T. noronhanum é capaz de manter estações de limpeza temporárias, próximas aos abrigos dos clientes, P. schomburgki diminui uma possível exposição aos predadores quando procura esta espécie versátil de limpador.
Keywords: Pempheris schomburgki; Thalassoma noronhanum; cleaning symbiosis; reef fishes; SW Atlantic